Assessment of awareness about plastic pollution and attitude regarding plastic bags usage among rural population of Kanchipuram, Tamil Nadu, India - Pandirajan, Shivashankari; Raja, V. Pragadeesh; Maruthupandiyan, Jasmine; Annadurai, Kalaivani (International Journal Of Community Medicine And Public Health, 2020)
Background: Plastic, although a simple synthetic polymer consisting of small molecules (monomers) linked together in a repetitive formation, is extremely versatile; with properties ranging from, resistance to corrosion, light weight, high strength, transparency, low toxicity to durability. The plastic used for domestic purpose nearly 500 billion plastic bags used each year.2 It is the slow poisoning to human health, animals and also the environment. Some years before plastic usage was few purposes only, over the past 60 years, plastics production and waste have dramatically increased, now days everyone using single use plastic bags for all use including cooked food packing, storage of drinking water and even storage of vegetables. The objective of this to assess the awareness regarding plastic pollution and to assess the attitude regarding plastic bag usage. Methods: A Community based cross sectional Study conducted among the population of residence, Sembakkam, Kancheepuram district, Tamil Nadu. The study duration between June to July 2019. Data collected through semi structured questionnaire from participants. Data Collected was entered in MS office excel and analyzed in SPSS version 21. Results: In the study, 67.5% (135) are males and 32.5% (65) are females. Mean age of the participants is 48.22 years (±14. 14). 86.5% (173) are literate and 13.5% (27) illiterate. In the study, participants 71% (142) answered plastic will cause health problem to animals and 24.5% (49) are not aware about health problem due to plastic. At the disposal of plastic 31% (62) replied burning of plastic which is followed by recycling the plastic 28% (56) (p<0.05) is the correct way of disposal. The majority of the participants, 90.5% (181) are supporting the banning of plastics and 5.5% (11) are not supporting the banning. Conclusions: Plastic usage has become a part of daily life, leading to the countless dumping of plastics. This in turn causes along with the environmental hazards, health hazards to both the humans and animals. The best recommendation is to reduce and reuse the daily usage of plastics. Strict Political and Administrative rules should be implemented and monitored.